2011
DOI: 10.1074/jbc.m111.261073
|View full text |Cite
|
Sign up to set email alerts
|

Receptor for Advanced Glycation End Products (RAGE) Prevents Endothelial Cell Membrane Resealing and Regulates F-actin Remodeling in a β-Catenin-dependent Manner

Abstract: Background: RAGE contributes to the vascular pathology associated with multiple disorders, including Alzheimer disease (AD), diabetic complications, and inflammatory conditions. However, the underlying mechanisms remain largely unknown. Results: RAGE expression in endothelial cells leads to an impaired plasma membrane resealing, altered F-actin remodeling, and increased ␤-catenin level. Conclusion: Through ␤-catenin, RAGE decreases F-actin stress fibers and prevents endothelial membrane repair in response to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 42 publications
1
28
0
Order By: Relevance
“…Treatment with either FPS‐ZM1 or RAP not only attenuated TDI‐induced airway inflammation and hyperresponsiveness but also reduced total, cytoplasmic and nuclear levels of β‐catenin, enhanced β‐catenin phosphorylation at Ser 33 / 37 /Thr 41 , which triggers ubiquitination, down‐regulated expression of β‐catenin targeted genes, and tended to keep β‐catenin at the cytomembrane, shifting β‐catenin from a signalling active pattern to an adhesive function. This was in agreement with what was found in endothelial cells (Xiong et al , ), but in disagreement with the data of Li et al . in osteoblastic cells, where there was a reduction of total β‐catenin level in response to Wnt3a‐CM after RAGE overexpression (Li et al , ).…”
Section: Discussionsupporting
confidence: 89%
“…Treatment with either FPS‐ZM1 or RAP not only attenuated TDI‐induced airway inflammation and hyperresponsiveness but also reduced total, cytoplasmic and nuclear levels of β‐catenin, enhanced β‐catenin phosphorylation at Ser 33 / 37 /Thr 41 , which triggers ubiquitination, down‐regulated expression of β‐catenin targeted genes, and tended to keep β‐catenin at the cytomembrane, shifting β‐catenin from a signalling active pattern to an adhesive function. This was in agreement with what was found in endothelial cells (Xiong et al , ), but in disagreement with the data of Li et al . in osteoblastic cells, where there was a reduction of total β‐catenin level in response to Wnt3a‐CM after RAGE overexpression (Li et al , ).…”
Section: Discussionsupporting
confidence: 89%
“…RAGE has been proposed to serve as a primary receptor for S100 proteins in the extracellular space, and plays an important role in S100A8- or S100A9-induced proliferation and migration of prostate and breast and colon cancer cells involving the MAPK/NF-κB signaling [18][20], [56], [70][71]. RAGE has been reported to increase the β-catenin level in human umbilical vein endothelial cell line (ECV–304) [72]. In addition, MAPK pathways have been shown to have unique and provocative roles that impact the Wnt/β-catenin signaling [73]-[76].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, induced levels of vasoconstrictor mediator endothelin-1 were induced to block Aβ-associated suppressed cerebral blood flow. A recent study by Xiong et al [165] reported that RAGE expression in human umbilical vein endothelial cell line (ECV-304) had prevented the endothelial cell membrane repair by activating β-catenin levels that resulted in reduced F-actin stress fibres and attenuated plasma membrane resealing [165]. Impaired glucose metabolism also plays a very important role in NFTs formation by promoting hyperphosphorylation of tau protein.…”
Section: Abnormal Glucose Metabolismmentioning
confidence: 97%